Implementasi Kurikulum Merdeka Belajar Perpektif Manajemen Pendidikan Islam (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
The purpose of writing is to find out an independent curriculum for the learning of our peers. The curriculum holds a key position in an educational institution, as it deals with determining the direction, content and educational process, which ultimately determines the type and quality of graduates of an institution. This research is a type of literature research. The approach used is a qualitative approach.  The results showed that Merdeka Learning returned educational literacy to its khittah as a strategic momentum to realize the goals of National Education so that religious spirituality literacy, self-control, personality, intelligence, noble character, and the skills of students in restoring education.